Training the Next Generation of Pharmacist Educators (NextGenRxEd): Outcomes from a Longitudinal 4-Year Teaching and Research Program - Candis M. Morello; Mark Bounthavong; Jan D. Hirsch (Pharmacy, 2025)
To combine didactic education with clinical and research experiences that would empower student pharmacists to consider postgraduate training and a career in pharmacy education or academics, in 2009, the Next Generation of Pharmacist Educators (NextGenRxEd) program, a four-year longitudinal education program, was implemented at the University of California San Diego Skaggs School of Pharmacy and Pharmaceutical Sciences. Directed by two pharmacist faculty, a clinician and researcher, student pharmacists were exposed to hands-on experience with clinical management, patient care, and research processes. A post-graduation survey was created and administered in Fall 2024 to evaluate outcomes for all student pharmacists who completed the program. Key performance indicators included the number of pharmacy students proceeding to postgraduate training, research practices, and pharmacist positions involving education and academics. During 2009–2024, 34 student pharmacists completed the NextGenRxEd program; 71% achieved postgraduate education (22 PGY1 residencies and two fellowships). Following quality improvement implementation, this percentage increased from 50% to 89%, for Classes 2009–2015 and 2016–2024, respectively. Overall, the PGY1 match rate was 92%, and 19 abstracts/posters and 10 manuscripts were published, respectively. The post-graduation survey response rate was 85%, with 93% of respondents reporting that they precepted PharmD students; 14% became faculty members, and 66% participated in research. The NextGenRxEd program provides a model whereby student pharmacists are equipped to obtain post-graduate education and pursue a career with a significant role in pharmacy education or academic pharmacy. This program has the potential to be implemented at other pharmacy schools/colleges to benefit faculty and student participants.